2004
DOI: 10.2460/ajvr.2004.65.1325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intracameral injection of preservative-free lidocaine on the anterior segment of the eyes in dogs

Abstract: No adverse ocular effects were detected after intracameral injection of preservative-free 1% or 2% lidocaine solution; thus, its use would be safe for intraocular pain management in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
(31 reference statements)
0
16
0
Order By: Relevance
“…15 Intracameral lidocaine injection is reportedly a safe means of providing additional analgesic effects in humans undergoing cataract surgery. 22 It is likely that lidocaine administered via this route has a remarkable analgesic effect in dogs undergoing intraocular surgery, but to the authors' knowledge, clinical studies on intracameral anesthesia in companion animals have not been reported. 16,[18][19][20] Intracamerally administered lidocaine is believed to diffuse into the iris and ciliary body and to be directly absorbed by the unmyelinated small nerve fibers located therein.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…15 Intracameral lidocaine injection is reportedly a safe means of providing additional analgesic effects in humans undergoing cataract surgery. 22 It is likely that lidocaine administered via this route has a remarkable analgesic effect in dogs undergoing intraocular surgery, but to the authors' knowledge, clinical studies on intracameral anesthesia in companion animals have not been reported. 16,[18][19][20] Intracamerally administered lidocaine is believed to diffuse into the iris and ciliary body and to be directly absorbed by the unmyelinated small nerve fibers located therein.…”
mentioning
confidence: 95%
“…3,14 Systemic use of lidocaine is still limited in animals with liver and heart problems. 22 The safety of intracamerally injected, preservative-free 1% or 2% lidocaine hydrochloride solution was established in another study. [16][17][18][19][20] Clinical trials in humans have revealed that intracameral lidocaine injection increases patient cooperation, compared with the effects of topical anesthetic administration alone.…”
mentioning
confidence: 99%
“…Intraocular local anesthetic has been investigated in dogs, with intracameral injection of preservative-free lidocaine producing no adverse effects on IOP or corneal thickness. 19 Intravenous infusion of lidocaine provided comparable analgesia to morphine infusion in dogs undergoing intraocular surgery with no side effects reported. 20 Loss of sensation to the globe and eyelids, as well as kinesis (immobility of the globe) can be achieved via retrobulbar local anesthetic administration.…”
Section: Local Anestheticsmentioning
confidence: 99%
“…In dogs, humans, and rabbits, no adverse ocular effects were detected after intracameral injection of preservative‐free 2% lidocaine. In humans, intracameral injection of 0.2‐0.3 mL of 1% lidocaine provides similar or even superior pupil dilation when compared to that obtained with the use of topical mydriatics .…”
Section: Introductionmentioning
confidence: 96%
“…However, intraoperative miosis is a complication that may occur in dogs and humans, resulting in inadequate equatorial lens exposure during lensectomy. Intracameral injection of 1:10 000 epinephrine and 1%‐2% lidocaine has been reported to be effective in the prevention of intraoperative miosis in dogs and humans . When injected intracamerally, lidocaine blocks the sodium channels on all nerve fibers and induces anesthesia and akinesia of the iris .…”
Section: Introductionmentioning
confidence: 99%